2017
DOI: 10.1007/s00784-017-2231-y
|View full text |Cite
|
Sign up to set email alerts
|

Progression level of extracapsular spread and tumor budding for cervical lymph node metastasis of OSCC

Abstract: This study indicated that the progression level and tumor budding of ECS for cervical lymph node metastasis were useful prognostic factors in OSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…Accumulating evidences have implicated tumor budding as a strong and valuable independent prognostic factor in many solid cancers . Moreover, evaluation of tumor budding in biopsy specimens also might provide useful prognostic information, indicating a promising clinical application for patient diagnosis and treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidences have implicated tumor budding as a strong and valuable independent prognostic factor in many solid cancers . Moreover, evaluation of tumor budding in biopsy specimens also might provide useful prognostic information, indicating a promising clinical application for patient diagnosis and treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Those budding cells represent a phenotype undergoing epithelial‐mesenchymal transition (EMT) or dedifferentiation . Accumulating evidence indicates that tumor budding is a valuable prognostic marker in many solid tumors due to it is correlated with more aggressive behavior and poor prognosis . In our previous studies, we found that tumor budding was an independent prognostic factor for OTSCC patients, particularly in T1/T2 stage .…”
Section: Introductionmentioning
confidence: 90%
“…Multivariate analysis in our study demonstrated that TB and ENE were significant independent predictors of LN recurrence (Table ). The study of Yamada et al proposed that the progression level of ENE and TB are useful prognostic factors in patients with OSCC . They divided the progression level of ENE into three types; type C, which was microscopically defined as tumor invasion to perinodal fat or muscle tissue, was associated with poorer prognoses based on the analyses of OS and RFS rates .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the level of ENE progression was not investigated in this study. The pathological level of ENE progression may be an important factor for predicting prognoses and the application of adjuvant therapy, although it is controversial . Previously, we demonstrated that DSS and RFS rates were significantly lower in patients with type C level of ENE progression, which was defined as microscopic tumor invasion into the perinodal fat or muscle tissue, than in patients with the other two types .…”
Section: Discussionmentioning
confidence: 90%